2018
DOI: 10.3389/fimmu.2018.01431
|View full text |Cite
|
Sign up to set email alerts
|

Roles of Myeloid and Lymphoid Cells in the Pathogenesis of Chronic Obstructive Pulmonary Disease

Abstract: Chronic obstructive pulmonary disease (COPD) is currently the third largest cause of human mortality in the world after stroke and heart disease. COPD is characterized by sustained inflammation of the airways, leading to destruction of lung tissue and declining pulmonary function. The main risk factor is known to be cigarette smoke currently. However, the strategies for prevention and treatment have not altered significantly for many years. A growing body of evidences indicates that the immune system plays a p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
23
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(28 citation statements)
references
References 99 publications
0
23
0
2
Order By: Relevance
“…Chronic obstructive pulmonary disease is associated with a characteristic pattern of chronic inflammation with increased numbers of neutrophils, macrophages and lymphocytes in the airway lumen in response to tissue damage and oxidative stress induced by cigarette smoke, although it remains to be clearly defined how this inflammation relates to clinical outcomes and disease progression, destruction of lung tissue and a decline in lung function. COPD is characterized by dysfunctional innate immunity with elevated AM numbers and AM‐derived cytokines and chemokines (CXCL8, TGF‐β, IL‐8, tumor necrosis factor alpha (TNFα) and reactive oxygen species) and CCL2 in the bronchoalveolar lavage and lung parenchyma of patients . This induces a rapid recruitment of other inflammatory cells including neutrophils and monocytes to the lungs, promoting disease progression.…”
Section: Chronic Lung Diseasesmentioning
confidence: 99%
See 1 more Smart Citation
“…Chronic obstructive pulmonary disease is associated with a characteristic pattern of chronic inflammation with increased numbers of neutrophils, macrophages and lymphocytes in the airway lumen in response to tissue damage and oxidative stress induced by cigarette smoke, although it remains to be clearly defined how this inflammation relates to clinical outcomes and disease progression, destruction of lung tissue and a decline in lung function. COPD is characterized by dysfunctional innate immunity with elevated AM numbers and AM‐derived cytokines and chemokines (CXCL8, TGF‐β, IL‐8, tumor necrosis factor alpha (TNFα) and reactive oxygen species) and CCL2 in the bronchoalveolar lavage and lung parenchyma of patients . This induces a rapid recruitment of other inflammatory cells including neutrophils and monocytes to the lungs, promoting disease progression.…”
Section: Chronic Lung Diseasesmentioning
confidence: 99%
“…COPD is characterized by dysfunctional innate immunity with elevated AM numbers and AMderived cytokines and chemokines (CXCL8, TGF-b, IL-8, tumor necrosis factor alpha (TNFa) and reactive oxygen species) and CCL2 in the bronchoalveolar lavage and lung parenchyma of patients. 51 This induces a rapid recruitment of other inflammatory cells including neutrophils and monocytes to the lungs, promoting disease progression. In mice, during cigarette smoke induced emphysema resident AM and recruited mononuclear phagocytes, contribute to the proinflammatory response by secreting TNFa and IL-6.…”
Section: Chronic Lung Diseasesmentioning
confidence: 99%
“…COPD is a common, progressive, inflammatory disease characterized by persistent and not fully reversible airflow limitation associated with an abnormal and deregulated chronic inflammatory response to noxious particles or gases [1][2][3]. Hallmarks of early stages of COPD include remodeling of small airways induced by persistently activated innate immune cells (alveolar macrophages, neutrophils, natural killer (NK), and DCs), while severe stages of COPD are characterized by the development of lung lymphoid follicles due to the enhanced activation of CD8+ cytotoxic T lymphocytes (CTLs) and CD4+ T helper cells and their crosstalk with B cells [4][5][6][7][8]. Continuous activation of resident and lunginfiltrated immune cells results in structural and functional changes in the inflamed lungs, including the narrowing of small airways, mucus hyperproduction, cilia dysfunction, and destruction of the lung parenchyma [9].…”
Section: Introductionmentioning
confidence: 99%
“…Despite the nature of immune system dysfunction in COPD remaining largely unknown, the crosstalk between innate and adaptive immunity has been shown previously to lead to increased severity [ 82 ]. Dysfunctional neutrophils chemoattraction lead to a premature diapedesis and neutrophilic elastase release that inhibits dendritic cells (DCs) maturation, increased mucin production, and decreased lung function [ 83 ]. The active respiratory epithelium releases MIP3 α /CCL20 that informs and recruits Th17 and DCs [ 84 ].…”
Section: Copd and Psoriasismentioning
confidence: 99%
“…In fact, in COPD, as well as in psoriasis, patients demonstrate an imbalance between Th17 and Treg, a finding confirmed by Wang and colleagues [ 84 ]. High levels of Th17 cells in small airway associate with poor function; in particular, IL-17A and IL-17F trigger and lead to development of neutrophilic airway inflammation [ 83 ]. This inflammatory pattern was also tested by Nadeem and colleagues who found that psoriasis triggers and is triggered by airway inflammation [ 70 ].…”
Section: Copd and Psoriasismentioning
confidence: 99%